2017
DOI: 10.2147/dddt.s130349
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative, apoptotic induction, and anti-migration effects of hemi-synthetic 1&prime;<em>S</em>-1&prime;-acetoxychavicol acetate analogs on MDA-MB-231 breast cancer cells

Abstract: Nine analogs of 1′S-1′-acetoxychavicol acetate (ACA) were hemi-synthesized and evaluated for their anticancer activities against seven human cancer cell lines. The aim of this study was to investigate the anti-proliferative, apoptotic, and anti-migration effects of these compounds and to explore the plausible underlying mechanisms of action. We found that ACA and all nine analogs were non toxic to human mammary epithelial cells (HMECs) used as normal control cells, and only ACA, 1′-acetoxyeugenol acetate (AEA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Increased proliferative capacity, decreased apoptosis, and enhanced invasion and migration are common biological features of tumor cells and the basis for tumor growth, metas tasis, and recurrence [26,27]. To further investigate the function of miR-103a-3p in thyroid cancer, we transfected the thyroid cancer cell line BHT101 with si-miR-103a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Increased proliferative capacity, decreased apoptosis, and enhanced invasion and migration are common biological features of tumor cells and the basis for tumor growth, metas tasis, and recurrence [26,27]. To further investigate the function of miR-103a-3p in thyroid cancer, we transfected the thyroid cancer cell line BHT101 with si-miR-103a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this hydroxyl group may not be a necessary component for these activities. In structure-activity relationship (SAR) studies of the compounds with similar skeletal structure, phenylpropanoids, the substitution of acetoxyl group at 4′ and 1 positions of phenylpropanoids (adjusted nomenclature similar to our study) are required for the strong inhibitory effects on β-hexosaminidase released from RBL-2H3 [31] and cytotoxic effects against MDA-MB-231 breast cancer cells [32]. For the inhibitory activity of NO production, the methoxyl group at 4′ - position and the hydroxyl group at 3- position with one glucopyranosyl moiety in the molecule are required [33].…”
Section: Discussionmentioning
confidence: 99%
“…Migration and invasion are the most important biological characteristics of malignant tumors and are the 2 main causes of death in tumor patients [ 16 ]. Migration and invasion of TNBC have been previously studied [ 26 , 27 ]. One study showed that the abilities of growth and invasion are enhanced in breast cancer cells with high expression of α1-AT [ 25 ].…”
Section: Discussionmentioning
confidence: 99%